2012
DOI: 10.1038/srep00984
|View full text |Cite
|
Sign up to set email alerts
|

Growth patterns for acervuli in human pineal gland

Abstract: Acervuli are calcified concretions in the pineal gland (PG). Particularly interesting are their incidence and size, which are believed to affect neurological disorders and many physiological functions of PG such as regulating circadian rhythm. Despite long investigations for a century, detailed growth mechanism of acervuli has yet to be studied. Here we study the growth morphology of acervuli in human PGs by a direct visualization in 3-dimension (3-D) using a synchrotron X-ray imaging method. For an entire PG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 33 publications
2
26
0
1
Order By: Relevance
“…Corpora Arenacea: se ha descrito también en la glándula pineal la presencia ocasional de acúmulos extracelulares calcificados de 47±28 µm denominados corpora arenacea, acérvulos cerebrales, arenilla cerebral o simplemente calcificaciones pineales (Kim et al, 2012). Se encuentran constituidas por fosfatos y carbonatos cálcicos que se depositan concéntricamente (Junqueria & Carneiro), además de sales de magnesio y hormonas polipeptídicas (Koshy & Vettivel, 2001a), estas luego de la formación concéntrica pueden crecer de dos maneras; "multiberry like" y como agregado (Kim et al).…”
Section: Astrocitos (Células Intersticiales Pinealocitos Tipo II Céunclassified
“…Corpora Arenacea: se ha descrito también en la glándula pineal la presencia ocasional de acúmulos extracelulares calcificados de 47±28 µm denominados corpora arenacea, acérvulos cerebrales, arenilla cerebral o simplemente calcificaciones pineales (Kim et al, 2012). Se encuentran constituidas por fosfatos y carbonatos cálcicos que se depositan concéntricamente (Junqueria & Carneiro), además de sales de magnesio y hormonas polipeptídicas (Koshy & Vettivel, 2001a), estas luego de la formación concéntrica pueden crecer de dos maneras; "multiberry like" y como agregado (Kim et al).…”
Section: Astrocitos (Células Intersticiales Pinealocitos Tipo II Céunclassified
“…Kim et al 11 found multiple concentrically calcified areas distributed throughout the pineal gland with centrally concentrated larger aggregates. Perivascular, tryptase-secreting mast cells have been found in areas where intrapineal calcium deposits originate, implicating these mast cells in the calcification process.…”
Section: Pineal Glandmentioning
confidence: 99%
“…X-ray imaging based on phase contrast and strongly collimated synchrotron X-rays 20 21 produces images of excellent quality due to strong edge enhancement between different regions 22 23 . Furthermore, synchrotron hard X-rays are highly penetrating, enabling us to examine large (> 1 × 1 × 1 mm 3 ) regions 24 25 26 of the lungs, not limited to subpleural regions. In addition, the projected radiographic images provide accurate information on alveolar size, different from histological images of sliced lung sections.…”
mentioning
confidence: 99%